Historians on Hamilton : how a blockbuster musical is restaging America's past - Romano, Renee Christine; Potter, Claire Bond, 1958- (Rutgers University Press, 2018)
Historians on ""Hamilton"" brings together a diverse collection of top scholars to explain the Hamilton phenomenon and explore what it might mean for our understanding of America's history. In short, lively essays, these experts assess what the musical got right, what it got wrong, and why it matters.